Legal Age of Marriage: A Socio-Science Review - Yulita, Nourma; Baso, Fatihani; Novita Sari, Kiki; ., Halmuniati; Aisyah Mu'min, Sitti; Novita Mudriani Djaoe, Andi (KnE Social Sciences, 2022)
The purpose of this paper was to examine the importance of the marriage law from various disciplines, in terms of the legal age of marriage. Data were collected by examining journals, books and other documents deemed relevant to the study. The findings indicated that the minimum age of marriage for girls, which was originally regulated in Law number 1 of 1974 concerning marriage, was 16 years. The Constitutional Court stated that this was unconstitutional and a violation of human rights, as well as a form of exploitation of children. Therefore, based on this decision, the Constitutional Court ordered legislators within a period of three years to make amendments to the Marriage Law, particularly with regard to the minimum age of marriage. In 2019, the issuance of a new rule of Article 7 paragraph (1) of Law number 16 of 2019 concerning amendments to Law number 1 of 1974 concerning marriage states that marriage is only permitted if the man and woman are a minimum of 19 years old. In adolescence, cervical cells have not yet grown in maturity. Sexual intercourse during adolescence increases the risk of being exposed to the human papilloma virus, the virus that causes cervical cancer. Another impact is that babies born to mothers who are under 18 years of age are more likely to have health issues. According to the BKKBN, the normal age for marriage is 25 years for men and 21 years for women. Early marriage not only has an impact on health, but also on the psychological survival of marriage. In addition, as a country where the majority of the population is Muslim, the age of marriage is also discussed in terms of religion and psychology. Keywords: legal competent, marriage, socio-science